Population dynamics of iron-oxidizing communities in pilot plants for the treatment of acid mine waters - Heinzel, Elke; Janneck, Eberhard; Glombitza, Franz; Schlömann, Michael; Seifert, Jana (Environmental science & technology, 2009)
The iron-oxidizing microbial community in two pilot plants for the treatment of acid mine water was monitored to investigate the influence of different process parameters such as pH, iron concentration, and retention time on the stability of the system to evaluate the applicability of this treatment technology on an industrial scale. The dynamics of the microbial populations were followed using T-RFLP (terminal restriction fragment length polymorphism) over a period of several months. For a more precise quantification, two TaqMan assays specific for the two prominent groups were developed and the relative abundance of these taxa in the iron-oxidizing community was verified by real-time PCR. The investigations revealed that the iron-oxidizing community was clearly dominated by two groups of Betaproteobacteria affiliated with the poorly known and not yet recognized species "Ferrovum myxofaciens" and with strains related to Gallionella ferruginea, respectively. These taxa dominated the microbial community during the whole investigation period and accelerated the oxidation of ferrous iron despite the changing characteristics of mine waters flowing into the plants. Thus, it is assumed that the treatment technology can also be applied to other mine sites and that these organisms play a crucial role in such treatment systems.